2010
DOI: 10.2224/sbp.2010.38.7.993
|View full text |Cite
|
Sign up to set email alerts
|

Gratitude for, and Regret Toward, Nature: Relationships to Proenvironmental Intent of University Students from Japan

Abstract: With university students from Japan as participants, the current study was undertaken to examine the hypothesis that gratitude for and/or regret toward nature positively relate to proenvironmental intent. On the basis of preliminary studies, we constructed a questionnaire containing scales aimed at measuring gratitude, regret, and general feelings or impressions about nature, as well as a scale of proenvironmental intent, which was adapted from frequently-used scales of proenvironmental attitude. The partial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 13 publications
0
11
0
4
Order By: Relevance
“…Esta sugerencia es formulada considerando que esta emoción disminuye los efectos negativos del materialismo e incrementa la satisfacción propia con la vida (Emmons & Mishra, 2010;Lambert et al, 2009;Naito et al, 2010;Polak & McCullough, 2006). Si una persona experimenta gratitud ante las acciones sociales de cuidado del agua es probable que se involucre en dicha conducta al seguir el modelo de otros.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Esta sugerencia es formulada considerando que esta emoción disminuye los efectos negativos del materialismo e incrementa la satisfacción propia con la vida (Emmons & Mishra, 2010;Lambert et al, 2009;Naito et al, 2010;Polak & McCullough, 2006). Si una persona experimenta gratitud ante las acciones sociales de cuidado del agua es probable que se involucre en dicha conducta al seguir el modelo de otros.…”
Section: Discussionunclassified
“…La gratitud incrementa las tendencias altruistas y motiva la conducta recíproca futura (Bartlett & DeSteno, 2006;Emmons & Mishra, 2010;Schmidt, 2008). Diversos estudios (Lambert, Fincham, Stillman, & Dean, 2009;Manríquez-Betanzos, Corral-Verdugo, Vanegas-Rico, TapiaFonllem, & Fraijo-Sing, 2016;Naito et al, 2010;Polak & McCullough, 2006) reportan que tendencias proambientales se relacionan con la gratitud.…”
Section: Introductionunclassified
“…This proposition has rarely been tested, however. An exception is Naito et al (2010), wherein Japanese participants reported their levels of gratefulness toward some natural entities and support for pro-environmental actions. A positive association was observed.…”
Section: Proposition 4 Gratitude To Nature Motivates Pro-environmental Behaviormentioning
confidence: 99%
“…A positive association was observed. However, Naito et al (2010) did not make the important distinction between trait gratitude and state gratitude, or consider the conceptual network of gratitude to nature. Methodologically, the influences of potential confounders were not controlled for and the causal effect on PEB was not examined.…”
Section: Proposition 4 Gratitude To Nature Motivates Pro-environmental Behaviormentioning
confidence: 99%
“…To the author's best knowledge, the only empirical research to date specifically looking at gratitude to nature has been Naito et al (2010), who found that gratitude towards nature was linked with pro-environmental behavior. However, no published research has investigated whether interpersonal gratitude can carry over to facilitate gratitude towards nature.…”
Section: Self-transcendent Emotions and Connectedness To Nature 16mentioning
confidence: 99%